2015
DOI: 10.4149/neo_2015_065
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 suppresses migration and invasion of thyroid carcinoma by targeting of Rac1

Abstract: Thyroid cancer, the most common primary endocrine malignancy in adult, imperatively requires new therapeutic studies that could target the molecular regulatory mechanism. Even though emerging evidence showed that long noncoding RNAs (Lnc-RNAs) are involved in different biological characteristic of malignant tumor, such as cell growth and apoptosis as well as cancer progression and metastasis. Limited data are available on the function of Lnc-RNAs in thyroid cancer invasion and metastasis. Among the 5 tested ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 25 publications
6
69
0
1
Order By: Relevance
“…For example, maternal expressed gene 3 (MEG3) was the first lncRNA demonstrated to act as a tumor suppressor in melanoma cells (21). In PTC, MEG3 was upregulated in carcinoma tissues compared with normal tissues and suppressed migration and invasion by targeting Ras-related C3 botulinum toxin substrate 1 (22). Papillary thyroid carcinoma susceptibility candidate 3 acts as a tumor suppressor in thyroid cancer cells and leads to marked significant inhibition of proliferation, cell cycle arrest and increased apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, maternal expressed gene 3 (MEG3) was the first lncRNA demonstrated to act as a tumor suppressor in melanoma cells (21). In PTC, MEG3 was upregulated in carcinoma tissues compared with normal tissues and suppressed migration and invasion by targeting Ras-related C3 botulinum toxin substrate 1 (22). Papillary thyroid carcinoma susceptibility candidate 3 acts as a tumor suppressor in thyroid cancer cells and leads to marked significant inhibition of proliferation, cell cycle arrest and increased apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…MEG3 is downregulated in PTC; downregulated MEG3 was significantly associated with lymph node metastasis. MEG3 is an important tumor suppressor in TC which suppresses migration and invasion by targeting Rac1 [48]. …”
Section: Maternally Expressed Genementioning
confidence: 99%
“…A number of studies have demonstrated that lncRNA MEG3, a tumor suppressor gene, was down-regulated in various cancers and was associated with poor prognosis (14)(15)(16)(17)(18). A previous study indicated that the expression of lncRN A MEG3 was clearly lower in osteosarcoma tissues compared with adjacent non-tumor tissues (19).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al suggested that MEG3 functions as a tumor suppressor in hepatoma cells through interacting with p53 protein (18). In addition to these studies, the role of MEG3 has been investigated in gallbladder cancer, NSCLC, neuroendocrine tumor, gastric cancer, thyroid carcinoma and so on (25,(14)(15)(16)(17). However, to the best of our knowledge, the potential roles of MEG3 in OS remain largely unknown.…”
mentioning
confidence: 99%